The Effect of Phosphorus Foliar Application on Some Physiological and Productive Characteristics of Strawberry Fruits - Kareem, Israa Hawyyiz (American Journal of Biology and Natural Sciences, 2026)
The present study was planned and designed to determine the effect of phosphorus spraying on the physiological characteristics and productivity of strawberries. The experiment was carried out in an unheated polyethylene tunnel 9m × 25m, strawberry transplants var. Festival were obtained from commercial nursery sources, planted in a raised-bed system at 20 × 80 cm spacing, mulched with black plastic, double row plants staggered 25 cm, on the 30 of October. Design of experiments The experiment is conducted as Randomized Complete Block Design (RCBD) under the factorial arrangement (3*3), with three replications. The results showed the effect of spraying with phosphorus on the number of fruits in strawberry plants. At concentration 0, the average number of fruits was 7.2±1.48 (fruit. plant-1), while at concentration 2 mg. L-1, the average number of fruits was 10.2±1.58 (fruit. plant-1), and the average number of fruits at concentration 4 mg. L-1 was 12.2±1.79 (fruit. plant-1). for, weight of fruits, At concentration 0, the average weight of fruits was 14.86±1.75 (gm. plant-1), while at concentration 2 mg. L-1, the average weight of fruits was 19.34±3.63 (gm. plant-1), and the average weight of fruits at concentration 4 mg. L-1 was 28.02±8.3 (gm. plant-1). for, total sugars of fruits, At concentration 0, the average total sugars of fruits were 3.04±0.14 (gm. 100 gm fresh weight-1), while at concentration 2 mg. L-1, the average total sugars of fruits were 3.77±0.06 (gm. 100 gm fresh weight-1), and the average total sugars of fruits at concentration 4 mg. L-1 was 4.13±0.11 (gm. 100 gm fresh weight-1). It was found that spraying with phosphorus plays an important role in improving the physiological and productive characteristics of strawberry fruits. Therefore, phosphorus can be used to improve strawberry productivity.